PhyMill is created to aid therapists and paediatric patients to undergo physiotherapy treatment - UMP, PNC (2020)
The sympathy towards children who face difficulties in controlling their bodies’ position and activation due to damage to their developing brain, or better known as cerebral palsy, inspired a group of Universiti Malaysia Pahang (UMP) researchers to develop the Smart Physio-Treadmill (PhyMill) to aid patients in training their walking movements.